Ghana : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2003)
All quantitative and structural performance criteria for end-June 2003 were observed. These positive results reflect several factors, including improved public expenditure management and strengthened revenue administration (offsetting delays in some of this year's new revenue measures), supported by a bumper cocoa harvest, higher world prices for cocoa and gold, and increased donor inflows. These plans should include civil service reform, energy sector restructuring, reform of land registration, and measures to strengthen governance. The goal of single-digit inflation remains achievable.